Pelatihan Pembuatan Kompos di Desa Pernek Kecamatan Moyo Hulu Kabupaten Sumbawa - Iga Maliga; Herni Hasifah; Rafi'ah Rafi'ah; Ana Lestari (Universitas Pahlawan Tuanku Tambusai, 2022)
Along with the increase in population, there is no doubt that waste is also increasing. Household waste is grouped into organic and inorganic groups. Unlike inorganic waste, which can still be sold or reused, organic waste is identical to the process of decay if it is not disposed of immediately. Pernek Village is one of the villages that has not had access to waste transportation by garbage trucks to the TPA. This village only relies on vacant land as a temporary TPA, and most people carry out the process of burning waste. This will create new problems for the environment. The service program was carried out in Pernek Village in September 2021 involving 20 program participants. Implementation of service from providing materials and demos of making compost. As much as 95% of community service participants do not understand and have never done composting. After the training process, 100% of the participants agreed to carry out the composting process at home. This is very important so that household waste can be reduced from home.